2019
DOI: 10.1016/j.paid.2018.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Who is the most demanding of them all? A multisource investigation of other-oriented perfectionism, socially prescribed perfectionism, and depressive symptoms

Abstract: Research at York St John (RaY) is an institutional repository. It supports the principles of open access by making the research outputs of the University available in digital form.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 22 publications
2
13
0
Order By: Relevance
“…More importantly, this study revealed the mediating effect of depression. Our findings supported the existential model of perfectionism and depressive symptoms [ 33 ] and the self-medication theory [ 37 ], and they were in line with previous findings that showed positive associations between perfectionism and psychological distress [ 32 , 34 ] and associations between depression and IA [ 47 , 48 ]. We provided rational explanations for these findings in the Chinese context.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…More importantly, this study revealed the mediating effect of depression. Our findings supported the existential model of perfectionism and depressive symptoms [ 33 ] and the self-medication theory [ 37 ], and they were in line with previous findings that showed positive associations between perfectionism and psychological distress [ 32 , 34 ] and associations between depression and IA [ 47 , 48 ]. We provided rational explanations for these findings in the Chinese context.…”
Section: Discussionsupporting
confidence: 92%
“…On the one hand, perfectionism was validated as a risk factor for multiple psychological disorders [ 31 , 32 ]. Theoretically, the existential model of perfectionism and depressive symptoms (EMPDS) could explain why perfectionism is predictive of psychological distress [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…This, in turn, allows for the investigation of several intriguing and vital questions. For example, evidence from research in adults is accumulating that the recipients of perfectionistic demands often suffer more than the source (e.g., Hewitt et al, 1995;Smith et al, 2017Smith et al, , 2019. Thus, research testing the extent to which one child's otheroriented perfectionism impacts another child's mental health would incrementally advance our understanding of the interpersonal consequences of perfectionism in youths.…”
Section: An Improved Understanding Of Other-oriented Perfectionism In...mentioning
confidence: 99%
“…Nonetheless, several studies have since found that other-oriented perfectionists can contribute to the depression symptoms of those around them. Namely, as mentioned, there is evidence that other-oriented perfectionism in mothers and siblings can contribute to depression symptoms in university-aged adults (e.g., Smith, Sherry, Glowacka, et al, 2019). Moreover, there are also recent suggestions that other-oriented perfectionism may be relevant to depression symptoms in specific cultural groups (Chen et al, 2017) and older samples of adults (Rnic et al, 2021).…”
Section: Evidence Of the Relevance Of Perfectionism To Depressionmentioning
confidence: 93%